2021
DOI: 10.1155/2021/1118728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sealing Ability of Direct versus Direct-Indirect Veneer Techniques: An In Vitro Study

Abstract: Backgrounds. Marginal discoloration, microleakage, wear, and marginal fractures are all prevalent problems with composite veneers, and this scenario leads the esthetic outcome to deteriorate with time, resulting in patient discontent. Aim of the Study. The study’s goal was to determine the marginal sealing ability of composite laminate veneers when employing two types of veneer techniques: direct and direct-indirect veneers, as well as two types of composite resin: nanohybrid and microfilled composite resin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another study, the type of composite used for the direct technique was evaluated by Mewan; he concluded that the nanohybrid composite used with an indirect–direct technique had maximum longevity compared with micro-filled composites. In both direct and indirect techniques the nanohybrid composites had decreased gingival microleakage compared with the micro-filled composites [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the type of composite used for the direct technique was evaluated by Mewan; he concluded that the nanohybrid composite used with an indirect–direct technique had maximum longevity compared with micro-filled composites. In both direct and indirect techniques the nanohybrid composites had decreased gingival microleakage compared with the micro-filled composites [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Semidirect resin composite veneers, fabricated extraorally on a stone model or special impression material, offer advantages over direct resin composite veneers, such as reduced polymerization shrinkage stress, excellent marginal adaptation, superior finishing/polishing, enhanced tooth detail reproduction, and precise interproximal contact points [19]. The longevity of semidirect veneers relies on selecting suitable surface bonding treatments, adhesive systems, and resin cement [26]. While their use in posterior teeth (onlays/inlays) is well-established [27], fewer cases have been reported for anterior teeth [12].…”
Section: Introductionmentioning
confidence: 99%